From summative training evaluation to estimating the outcomes of training A study of training transfer during primary and middle school teachers professional development - Pisanu, Francesco (Formazione & insegnamento, 2015)
The main purpose of this paper is an analysis of some factors in the learning process, often underestimated in research and practice, that affect individual and organizational performance of teachers inside school context. These factors are related to the process of transfer of learning, from training to workplace in everyday life. There are two main research questions considered in this work. What are the factors (at individual, organizational and training process level) that typify the transfer of training of teachers engaged in professional development activities? Are there any variations in the levels of training transfer perceived by teachers during a school year, just after the application of learning on the job? The context of the study presented here is an action research project on the use of devices of personalization and differentiation in classroom daily activities, which was attended by 20 teachers from three schools in the Province of Trento. Through transfer of training self-report (questionnaire) and behavioral measures (structured classroom observation), few “bad” transfer related issues were identified at the organizational level, such as low principals support to teachers in introducing new teaching methods (perceived measure), and teachers self imposed misbehaviours in changing traditional forms of teaching (observed measure).